1985
DOI: 10.1111/j.1095-8649.1985.tb04016.x
|View full text |Cite
|
Sign up to set email alerts
|

The food and feeding habits of the goatfish, Parupeneus barberinus (Lacepede), from Aqaba, Jordan

Abstract: The food habits of the goatfish, Parupeneus barberinus, from Aqaba were studied. A total of 166 fish over a range of 15 to 27.7cm and representing five age groups were examined. The major dietary components, based on occurrence, were crustaceans (82.6%), sand (71.1 Yy), foramniferans (%%), detritus (52.3%) and polychaetes (49%). Based on gravimetric analysis, crustaceans and sand were the major food components comprising 54.4% and 23.3% of the total food weight respectively. The food consumption decreased from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1995
1995
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 11 publications
1
10
0
Order By: Relevance
“…All species of goatfish are benthic carnivores (Lee, 1973;Hobson, 1974;Munro, 1976;Caragitsou & Tsimenidis, 1982a,b;Wahbeh & Ajiad, 1985;Golani & Galil, 1991;Vassilopoulou & Papaconstantinou, 1993;Golani, 1994). ‡Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All species of goatfish are benthic carnivores (Lee, 1973;Hobson, 1974;Munro, 1976;Caragitsou & Tsimenidis, 1982a,b;Wahbeh & Ajiad, 1985;Golani & Galil, 1991;Vassilopoulou & Papaconstantinou, 1993;Golani, 1994). ‡Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Werner & Gilliam, 1984;Ross, 1986;Platell et al, 1997;Platell & Potter, 1998), which are important for understanding fully how co-occurring species might interact. Furthermore, only three studies on individual species of mullids have reported changes in dietary composition with increasing body size (Lee, 1973;Wahbeh & Ajiad, 1985;Vassilopoulou & Papaconstantinou, 1993). In none of these studies were multivariate analyses used to evaluate the influence of factors such as location and season on diet.…”
Section: Introductionmentioning
confidence: 99%
“…Red Sea goatfish, Parupeneus forsskali, ontogenetic shifts in prey search, resource use, shoaling tendency and association with other species based on a field investigation of four size/age classes in the Gulf of Aqaba, Northern Red Sea (Uiblein 1991). Food selection information is based on Wahbeh & Ajiad (1985).…”
Section: Habitat Modificationmentioning
confidence: 99%
“…Intermediate size classes were more often found on hard substrates and were also more often associated with other species. One advantage for the goatfishes to form mixed-species flocks on a hard substrate would be to gain access to damselfish territories where they may dislodge fish eggs, a favourite food source during this life-history period (Wahbeh & Ajiad 1985; Figure 2). …”
Section: Multi-species Foraging Associationsmentioning
confidence: 99%
See 1 more Smart Citation